Coordination and reorganization of security institutions - Bakreski, Oliver; Miloshevska, Tanja; Bargieva, L. (University St. Kliment Ohridski - Bitola and Faculty of Security, Skopje, 2018)
The coordination of the security sector is exceptionally important because it enables the necessary synchronization of the security institutions, which leads to overall adjustment of the activities in order to maintain a balanced system of relations and proper transformation of the security institutions. The issues which merit to be analyzed in the context of foreseeing whether and how the coordination of the security community in the country, and in general between the institutions in charge of maintaining the security of the country is achieved, point out to: the existence or the nonexistence of coordination. Hence, this paper has a dual relevance. First, it designates the existence or the nonexistence of security sector coordination in the Republic of Macedonia. Here, as referent and starting contexts are taken the practical solutions in the segment of coordination provided by the country, synthesized and generalized in the security system of the Republic of Macedonia. Second, locating the problem and giving recommendations for coordination improvement.
Keywords: transformation, subjectivism, security sector, re-organization.